Master track of Senckenberg SEN2212 cruise on 2022-05-03 - González, Everardo; Kampmeier, Mareike; Greinert, Jens (GEOMAR - Helmholtz Centre for Ocean Research Kiel, 2023)
Raw navigation data acquired by the navigation system of the Senckenberg during the expedition SEN2212 which took place on the 3rd of May 2022 between Jade and Wangerooge in the German North Sea coast. The track was acquired with a Hemisphere Cresent R131RCVR GPS antenna and recorded with the Ocean Floor Observation Protocol (OFOP) software. No further processing was undertaken. The data is provided as a master track with 1 sec resolution derived from the position sensors' data. This cruise was an activity of the CONMAR project of the DAM research mission "Protection and Sustainable Use of Marine Areas".
Keywords: Course Over Ground; position; SEN2212; Senckenberg; Velocity Over Ground